2023
DOI: 10.3389/fcell.2022.1020609
|View full text |Cite
|
Sign up to set email alerts
|

PHIP-associated Chung-Jansen syndrome: Report of 23 new individuals

Abstract: In 2016 and 2018, Chung, Jansen and others described a new syndrome caused by haploinsufficiency of PHIP (pleckstrin homology domain interacting protein, OMIM *612,870) and mainly characterized by developmental delay (DD), learning difficulties/intellectual disability (ID), behavioral abnormalities, facial dysmorphism and obesity (CHUJANS, OMIM #617991). So far, PHIP alterations appear to be a rare cause of DD/ID. “Omics” technologies such as exome sequencing or array analyses have led to the identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Compared to the previous studies (Table 4), we found comparable results with developmental delay in 85% (Jansen et al, 2018; Kampmeier et al, 2022). Our cohort had no report of developmental regression.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Compared to the previous studies (Table 4), we found comparable results with developmental delay in 85% (Jansen et al, 2018; Kampmeier et al, 2022). Our cohort had no report of developmental regression.…”
Section: Discussionsupporting
confidence: 83%
“…We started to observe obesity/overweight at the age of seven, and the frequency of obesity/overweight increases with age. Kampmeier et al (2022) found that the incidence of obesity/overweight rose sharply during puberty. However, Kampmeier et al also found that some individuals as young as 5 years old were already obese/overweight.…”
Section: Discussionmentioning
confidence: 99%
“…There were no clear clusters for each type of variant. This figure was published in the original paper (Kampmeier et al, 2023) as Figure 5.…”
Section: Facial Phenotype Descriptors Delineate Facial Gestalt Of Dis...mentioning
confidence: 99%
“…The same concept of similarity measurement can also be applied to compare different disorders. Kampmeier et al utilized tSNE to visualize the clustering among the patients with PHIP, CUL4B , and Prader‐Willi syndrome (PWS; OMIM #176270) in two‐dimensional space (Kampmeier et al, 2023). The tSNE plot showed that three groups formed three clusters, although some CUL4B patients were similar to PWS patients.…”
Section: Facial Phenotype Descriptors Delineate Facial Gestalt Of Dis...mentioning
confidence: 99%
“…With the recent advances in computer vision, many AI‐based applications have begun to be used to facilitate diagnosis through facial image analysis (Dingemans et al., 2022; Dudding‐Byth et al., 2017; Gurovich et al., 2019; Hsieh et al., 2022; Hustinx et al., 2023; Porras et al., 2021; Sümer et al., 2023) and to further delineate the phenotypes of novel diseases (Aerden et al., 2023; Asif et al., 2022; Averdunk et al., 2023; Ebstein et al., 2023; Guo et al., 2022; Kampmeier et al., 2022; Knaus et al., 2018; Lyon et al., 2023; Marbach et al., 2019; Oppermann et al., 2023; Pantel et al., 2018).…”
Section: Commentarymentioning
confidence: 99%